Ureteral injury due to Kirschner wire in a five-year-old girl: a case report - Altın, M. Ali; Gündoğdu, Z. Hülya (The Turkish Journal of Pediatrics, 1994)
Traumatic injury to the ureter in childhood is uncommon, and since it is not associated with hematuria may remain undiagnosed for a relatively long period of time. In this paper we reported the case of a five-year-old girl who had ureteral injury due to Kirschner wire application for hip dislocation. We drew attention to the fact that pelvic interventions may be complicated by ureteral injury, and intravenous pyelography is a useful tool to reach the final diagnosis.